2016
DOI: 10.1016/j.celrep.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome of Coexisting BaAka Pygmies and Bantu Reflects Gradients of Traditional Subsistence Patterns

Abstract: To understand how the gut microbiome is impacted by human adaptation to varying environments, we explored gut bacterial communities in the BaAka rainforest hunter-gatherers and their agriculturalist Bantu neighbors in the Central African Republic. Although the microbiome of both groups is compositionally similar, hunter-gatherers harbor increased abundance of Prevotellaceae, Treponema, and Clostridiaceae, while the Bantu gut microbiome is dominated by Firmicutes. Comparisons with US Americans reveal microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
203
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(270 citation statements)
references
References 54 publications
26
203
2
4
Order By: Relevance
“…While a relatively small study cohort of 29 individuals from each group, sequencing data revealed that the gut microbiota composition of the BaAka pygmies is more similar to the known composition of wild primates, whereas the Bantu composition is more similar to Western microbiomes [19]. The authors suggest that these populations may elucidate changes that occurred in the human gut microbiome in response to evolving agricultural and dietary practices and the resulting modern day Western diet.…”
Section: Evolution Of the Western Diet And Microbial Selectionmentioning
confidence: 94%
“…While a relatively small study cohort of 29 individuals from each group, sequencing data revealed that the gut microbiota composition of the BaAka pygmies is more similar to the known composition of wild primates, whereas the Bantu composition is more similar to Western microbiomes [19]. The authors suggest that these populations may elucidate changes that occurred in the human gut microbiome in response to evolving agricultural and dietary practices and the resulting modern day Western diet.…”
Section: Evolution Of the Western Diet And Microbial Selectionmentioning
confidence: 94%
“…Gomez et al . [78 • ] analyzed metabolites and gut microbiota samples from Central African Republic populations, and showed that while the gut microbiomes of CAHG (BaAka) and Bantu generally looked distinct from those of U.S. Americans, the settled, agriculturalist Bantu had gut microbiome profiles that were more similar to U.S. guts than those of the BaAka [78 • ]. Although these studies indicate that subsistence practice and pathogen infection shape the microbial composition of the gut, expanding this research to include more studies of ancient human microbial communities could elucidate differences between modern and ancient microbe structure and function, evidencing adaptations to changing environmental pressures and dietary shifts during long term human evolution.…”
Section: Adaptation In Sub-saharan Africamentioning
confidence: 99%
“…Nonetheless, other reports point to an infant gut resistome that is unique and different from that of the mothers, and that includes resistance to broad-spectrum β-lactam antibiotics, suggesting that early environmental determinants (different from maternal ones) also shape AMR development in the infant gut [58, 59]. In fact, lifestyle factors related to subsistence, diet and other cultural drivers strongly shape the GI microbiome [60, 61]. …”
Section: Introductionmentioning
confidence: 99%